Equity and law - Falcón y Tella, María José (Martinus Nijhoff Publishers, 2008)
Presents a study of the different types of equity throughout history and in the different legal systems; the concept, content, limits, functions and types of equity; and, the relationship between equity and related ideas, and equity in all the branches of the legal order.
Keywords: Equity.; Law -- Philosophy.; LAW -- Jurisprudence.; LAW -- General Practice.; LAW -- Reference.; LAW -- Essays.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; Equity; Law -- Philosophy; Philosophy.; Philosophy of law.